Report of the Executive Board Working Group on IMF Corporate Governance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
On May 21, 2008, the Executive Board discussed the report of the Independent Evaluation Office (IEO) on 'Aspects of IMF Corporate Governance - Including the Role of the Executive Board'. The Joint Statement issued by the Executive Board and the Managing Director following the Board discussion noted that many of the issues raised by the IEO were complex and interrelated. Furthermore, the follow-up discussion would require the engagement of all parties at many different levels, involving not only the Executive Board and Management, but also the Fund's membership and other stakeholders more broadly. This report presents the recommendations of the Working Group, based on work carried out during June-July 2008. The proposed detailed work plan in Table 1 is an integral part of this report. Section II of the report describes the work streams. Section III discusses issues beyond the IEO report and proposes a monitoring process. Section IV presents the recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet